Aboveground and Belowground Male Population of the Invasive Citrus Mealybug Delottococcus aberiae De Lotto (Hemiptera: Pseudococcidae) - Rosa Vercher; Adrián Sánchez-Domingo; Isabel Escriche (Insects, 2025)
The invasive Delottococcus aberiae is one of the most harmful mealybugs on citrus in Spain, since it causes deformations and the premature falling of fruits in citrus orchards. To improve control strategies, this study evaluates its population above- and belowground, their distribution in the soil in addition to identifying natural enemies. The distribution in the soil of emerged males varies significantly with the distance to the tree trunks with an annual average number of 0.95 males/trap/day at 0.5 m, and ranging between 0.25 and 0.32 at 1 m, 1.5 m and 2 m. There is a consistent emergence of males throughout the year, both above- and belowground, with four distinct peaks, the first two occurring in February and April. This observation is essential to manage fruit damages that follows between March and June. Among the natural enemies detected belowground the following are highlighted: Bdellidae mites (52%), Hymenoptera parasitoids (16%) and spiders (11%). When implementing IPM strategies, emphasis should be placed on adequate soil management (crops, mulching, or the release of natural enemies) and to the appearance of first generation. We propose a belowground population sampling method as a simple and practical tool to quantify this pest’s the winter and spring populations, which remain undetectable using current methodologies.